Correlation of Knowledge and Family Support with Treatment Compliance of Tuberculosis Sufferers - Eka Yulianita, Marisna; Marhani; Yuliana Kasma, Andi (AACENDIKIA: Journal of Nursing, 2023)
Introduction: The World Health Organization (WHO) records that around 1.7 million people die from pulmonary tuberculosis in the world, while in Indonesia it is estimated that 92,700 people die or around 11 people per hour due to this disease. One of the causes of death from tuberculosis was due to low compliance which ends in treatment failure. The aim of this research is to analyze the factors that influence the fulfillment of treatment for tuberculosis patients at the Bajeng Community Health Center, Gowa Regency. Methods: This type of research is analytical observational research with a cross sectional research design. The sample for this study was 93 outpatient tuberculosis patients obtained using the Accidental Sampling technique. Results: The results of the Spearman correlation test show that knowledge and family support has a positive correlation with the availability of treatment for tuberculosis patients (p= 0.000) (r= 0.852). The correlation strength of knowledge was 0.852 and family support was 0.742. Conclusions: The conclusion of this research is that good knowledge and family support will increase treatment compliance for tuberculosis sufferers at the Bajeng Community Health Center, Gowa Regency. It is recommended that there be support and motivation for tuberculosis patients in undergoing treatment.